2-D Reconstruction of Breast Image Using Forward-Backward Time-Stepping Method for Breast Tumour Detection - Elizabeth, M.; Hong Ping, K.; Ng, S.W; Wan Zainal Abidin, W.A; Masri, T.; Othman, A.K.; Moriyama, T.; Takenaka, T. (IEEE, 2012)
In this paper, time-domain inverse-scattering technique referred to as Forward-Backward Time-Stepping (FBTS) method is applied to microwave imaging breast cancer detection. The FBTS algorithm is implemented in C++ language executed in a single computer by developing the time domain form of the FDTD. The ability to detect as small as 4mm of the embedded tumour and reconstructing the image in twodimensional with significant contrast in the dielectric properties of normal breast tissue and malignant tumour is presented in this paper.